Carbon emissions in countries that failed to ratify the intended nationally determined contributions: A case study of Kyrgyzstan. (1st February 2020) - Yang, Pu; Cui, Can; Li, Lixu; Chen, Weijian; Shi, Yaping; Mi, Zhifu; Guan, Dabo
Abstract: The Paris Agreement aims to increase global participation in climate change actions, yet attentions are not equally given among countries. The knowledge gap remains in understanding the structure and drivers of the emission in small developing countries. Eighteen countries have failed to ratify their Intended National Determined Contributions (INDCs) as an officially recognized emission target. Among these countries, we chose Kyrgyzstan as a case to construct its emission inventories from both production-based and consumption-based perspectives and to identify the drivers of emission changes using structural decomposition analysis (SDA). The empirical results revealed that CO2 emissions in Kyrgyzstan depicted a wavelike rise from 2007 to 2015, whilst the production structure contributed to 14% of the production-based CO2 emission growth from 2012 to 2015. As a net emission importer, Kyrgyzstan transferred large quantities of CO2 emissions to China and Russia through imports. However, if all manufacturing imports were produced within Kyrgyzstan, the emission would be over five times compared to the current level. It is helpful to reduce global emissions for Kyrgyzstan to import goods from other countries whose carbon intensities are lower. Overall, this study highlights the need to focus on these countries' failure to ratify INDCs while calling the Paris Agreement to provide a better understanding and mitigation mechanism for these small developing countries. Highlights: We develop production- and consumption-based CO2 emissions inventory for Kyrgyzstan. The changes in production structure increasingly contribute to emission growth. Kyrgyzstan transfers CO2 emissions to China and Russia through imports. More attention is needed to understand the emissions in small developing countries.